Impact of protease and lipase activities on quality of Swedish raw milk. (August 2020) - Glantz, Maria; Rosenlöw, Maria; Lindmark-Månsson, Helena; Buhelt Johansen, Lene; Hartmann, Julia; Höjer, Annika; Waak, Elisabet; Löfgren, Richard; Hallin Saedén, Karin; Svensson, Cecilia; Svensson, Birgitta; Lindau, Jeanette; et al.
Abstract: An increasing demand for dairy products with long shelf-life is foreseen. A limiting factor for maintaining high quality of these products is the activity of spoilage enzymes during storage. Lipase and protease activities in Swedish raw milk at farm and dairy level were investigated, analysing milk samples from three geographical regions and two seasons. Lipase activity in milk at farm level was affected by regional and seasonal variations, whereas at dairy level only season had an effect. Lipase activity was positively correlated with ionic calcium. For protease activity, no effect of either region or season was seen. Degradation products, e.g., free fatty acids, peptides and plasmin proteolysis products, varied differently between season and geographical origin at both farm and dairy level. The results indicate that lipase and protease activities are important for raw milk quality, while ionic calcium might be a future indicator for milk fat stability.